2007
DOI: 10.1210/jc.2007-0868
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Anti-Müllerian Hormone Level during Low-Dose Recombinant Follicular-Stimulating Hormone Therapy for Anovulation in Polycystic Ovary Syndrome

Abstract: These data suggest that in anovulatory women with PCOS, gently increasing the serum FSH level reduces the AMH excess, thus relieving the inhibition from the latter on aromatase expression by selectable follicles and allowing the emergence of a dominant follicle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 30 publications
4
23
1
1
Order By: Relevance
“…A plausible hypothesis for this figure is that the increased AMH levels in PCOS are the results of the increased number of small ovarian follicles [29,30]. In this regard, a direct and a significant correlation between follicle number and serum AMH levels has been demonstrated by some authors [8-10,12], even if the hypotheses provided for this correlation were not univocal [27,28]. …”
Section: Discussionmentioning
confidence: 99%
“…A plausible hypothesis for this figure is that the increased AMH levels in PCOS are the results of the increased number of small ovarian follicles [29,30]. In this regard, a direct and a significant correlation between follicle number and serum AMH levels has been demonstrated by some authors [8-10,12], even if the hypotheses provided for this correlation were not univocal [27,28]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in patients with PCOS by Li et al [15] reported a mean AMH level of 9.85 ng/mL while Catteau-Jonard et al [11] reported 6.59 ng/mL. Piltonen et al [16] concluded that the AMH level in patients with PCOS was always two or three times higher than the normal population (16–44 years).…”
Section: Discussionmentioning
confidence: 99%
“…This was demonstrated in a study using continuous low dose FSH recombinant therapy that resulted in a significantly decreased AMH level in the follicle. It was suggested that a decreased AMH level would lead to the suppression of the inhibitory mechanism in the follicle; thus it could then develop into a dominant follicle [11]. Amer et al [19] reported that after laparoscopic ovarian diathermy, the AMH level in subjects with ovulation was 25% lower than subjects with no ovulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catteau-Jonard et al investigated whether reduction of AMH production occurs in CC-resistant women with PCOS with at least one dominant follicle after low-dose step-up administration of FSH [27]. They found that a decrease in the serum AMH level was concomitant with the appearance of a dominant follicle.…”
Section: Discussionmentioning
confidence: 99%